Species-Specific PCR for Identification of Common Contaminant Mollicutes in Cell Culture - Kong, Fanrong (American Society for Microbiology, 2001)
Mycoplasma arginini, M. fermentans, M. hyorhinis, M. orale, and Acholeplasma laidlawii are the members of the class Mollicutes most commonly found in contaminated cell cultures. Previous studies have shown that the published PCR primer pairs designed to detect mollicutes in cell cultures are not entirely specific. The 16S rRNA gene, the 16S-23S rRNA intergenic spacer region, and the 5′ end of the 23S rRNA gene, as a whole, are promising targets for design of mollicute species-specific primer pairs. We analyzed the 16S rRNA genes, the 16S-23S rRNA intergenic spacer regions, and the 5′ end of the 23S rRNA genes of these mollicutes and developed PCR methods for species identification based on these regions. Using high melting temperatures, we developed a rapid-cycle PCR for detection and identification of contaminant mollicutes. Previously published, putative mollicute-specific primers amplified DNA from 73 contaminated cell lines, but the presence of mollicutes was confirmed by species-specific PCR in only 60. Sequences of the remaining 13 amplicons were identified as those of gram-positive bacterial species. Species-specific PCR primers are needed to confirm the presence of mollicutes in specimens and for identification, if required.